1993
DOI: 10.1084/jem.177.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of pemphigus vulgaris antibody to the major histocompatibility complex in healthy relatives of patients.

Abstract: SummaryPemphigus vulgaris (PV) is an autoimmune disease caused by high concentrations of antibody to an epidermal cadherin. The disease is associated with two kinds of HLA-DR4, DQ8 haplotypes dominantly distributed among Jewish patients, and these plus DR6, DQ5 haplotypes in nonJewish patients. Low levels of the PV antibody were found in 48% of a total of 120 asymptomatic parents, children, and siblings of 31 patients, thus exhibiting dominant inheritance. The inheritance of these low levels of antibody in asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
5

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 23 publications
3
51
0
5
Order By: Relevance
“…However, the nature of these genetic factors differs for different antibody responses. For example, inheritance of the ability to mount an autoantibody response to epidermal cadherin in healthy relatives of patients with pemphigus vulgaris is linked to HLA [41]. Similarly, HLA-DR and DQ genes control the autoimmune response to DNA topoisomerase I in systemic sclerosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, the nature of these genetic factors differs for different antibody responses. For example, inheritance of the ability to mount an autoantibody response to epidermal cadherin in healthy relatives of patients with pemphigus vulgaris is linked to HLA [41]. Similarly, HLA-DR and DQ genes control the autoimmune response to DNA topoisomerase I in systemic sclerosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Dsg3-reactive T cells could be isolated from healthy individuals with PV-associated HLA alleles (11). In addition, low level of anti-Dsg3 Ab was detected in healthy relatives of PV patients (28,29). In a BCR transgenic model, a Dsg3-specific B cell escaped from tolerance mechanism (30).…”
Section: Discussionmentioning
confidence: 99%
“…Pemphigus vulgaris (PV) is caused by autoAb against the extracellular domain (ECD) of desmoglein 3 (Dsg3), while pemphigus foliaceus, a clinically less severe disorder, is caused by autoAb against the ECD of Dsg1 (1,3). AutoAb production in PV is polyclonal, and most autoAb are of the IgG4 subclass in pemphigus patients with active disease (4), while patients with chronic disease have autoAb of the IgG1 and IgG4 subtypes, and healthy relatives of PV patients and healthy carriers of PV-prevalent HLA class II alleles appear to have low levels of Dsg3-reactive IgG1 (4,5).…”
mentioning
confidence: 99%